Satisfação com a vida: uma explicação pautada na crença no mundo justo e nos valores humanos - Nascimento, Anderson Mesquita do (2016)
This work aims to test a mediation model where life satisfaction is explained by human values, taking the belief in a just world as mediator of this relationship, which has been pursued over three studies. In study 1, it was sought to determine whether the belief in just world scale version showed evidence of validity and reliability in the Brazilian context. In this study, participated a sample of 300 individuals, recruited by criteria of convenience (non-probabilistic) through social networks and contacted via email. The results showed that the data can be presented in a structure with two factors, with internal consistency indices to conducting research. In study 2, it was tried to check the value correlates of belief in a just world, observing what subfunctions could predict such beliefs. To this end, it counted on the participation of 1294 people from four countries, two in South America (Argentina and Chile) and two from Europe (Belgium and Bulgaria). The results showed that the belief in just world has relation with the normative values, which can be observed in the samples from all the countries. However, this was not the only verified relationship because the two countries in South America investigated showed similar correlation patterns with each other, with respect to the subfunction suprapersonal, existence, interactive and normative. The countries from Europe, showed distinct correlation patterns with each other, and in Belgium, as well as normative subfunction, the CMJ was related to the interactive values and a relationship that had not been seen in previous studied, with the promotion values. Bulgaria already has relations with the interactive subfunction, normative and excitiment. Finally, in study 3 it was sought to verify whether the belief in a just world would mediate the relationship between human values and life satisfaction in a second Brazilian sample. To this end participated 331 people, including those from the general population and university students, who answered the questionnaires available in the same way of previous studies. The results showed that the factorial structure of the scale Belief in Just World showed to be adequate. Moreover, correlation tests were performed for the three variables. It was observed that the life satisfaction was positively correlated with the interactive and normative subfunction and with beliefs in just world general and personal, as well as negative correlation with the belief in an unjust world. Belief in a just world had relationship with the interactive, excitement and normative subfunctions, being greater magnitude with the latter. Therefore, it was seemed consistent to test a model in which the beliefs in the just world personal and general mediate the relationship between the normative values and life satisfaction. The results showed that, in fact, there is mediation, which is indirect, given the fact that with the entry of beliefs in the model, the normative subfunction continued to post directly related to life satisfaction, even with the inclusion of belief in just world. In view of the presented results, it trusts that the present work contributes to the understanding of the life satisfaction and belief in a just world, being the latter little explored in Brazil.